Theoretical value of management accounting and its place in enterprise management - Trunkina, L.V.; Shakeyev, S.S.; Reidolda, S.; Ahanova , N.E. (BUKETOV BUSINESS REVIEW, 2019)
The article analyzes the theoretical basis of the management problem, analyzed the opinion of various scientists. The place of management accounting is defined in the enterprise management system.The relevance of the topic is that the theoretical value of General management accounting and the need to determine its place in the management of the enterprise. To date, there are two main issues in the field of cost management and financial performance of the enterprise. The first is to reorient the theory and practice of the domestic accounting system in market conditions to perform new tasks facing the issue of enterprise management. Secondly, the creation of an adapted system for obtaining information on costs, the application of a new approach to cost calculation, calculation of financial results, as well as methods of analysis and control, and the adoption of effective management decisions on this basis. Management accounting in most Kazakh enterprises is not conducted or is very poorly developed. This is mainly due to the lack of a unified methodological framework and guidelines for the organization of management accounting in certain sectors of the domestic economy, as well as the stage of its formation and development in domestic practice. At the same time, currently enterprises in the Republic of Kazakhstan are in need of an effective management accounting system functioning in the conditions of competition and viability. In this regard, it was noted that a detailed study of the management accounting system was of particular importance for enterprises.